Pengaruh Program Gratis Ongkir terhadap Volume Penjualan Produk di Unit Usaha Ibbien Mart Ponpes Bumi Damai al-Muhibbin - Zaki Ahmad Fauzan; Muhammad Ali Ridho; Aslihah Aslihah; Bekti Widyaningsih (YASIN, 2026)
Pesantren-based business units need to develop adaptive marketing strategies to increase competitiveness and sales volume, including through free shipping programs that can reduce consumers’ shopping cost burdens. This study aims to analyze the effect of the free shipping program on product sales volume at the Ibbien Mart Business Unit of Pondok Pesantren Bumi Damai Al-Muhibbin. This study used a quantitative approach involving consumers and employees of Ibbien Mart as the research population. The sample consisted of 52 respondents selected using simple random sampling. Data were collected through observation, questionnaires, and documentation, then analyzed through validity testing, reliability testing, classical assumption testing, and hypothesis testing in the form of t-tests and F-tests with the assistance of the SPSS program. The results showed that the free shipping program had a positive and significant effect on sales volume, with a calculated t-value of 90.161, which was greater than the table t-value of 0.254, and a significance value of 0.000 < 0.05. The coefficient of determination (R²) value of 0.994 showed that the free shipping program contributed 99.4% to changes in sales volume, while 0.6% was influenced by other factors outside the research model. The conclusion of this study affirms that the free shipping program can serve as an effective marketing strategy to increase sales volume in pesantren-based business units. The implications of this study indicate the importance of optimizing marketing strategies aligned with the principles of Islamic economics, such as justice, transparency, and public benefit, so that promotional programs not only increase sales but also support business sustainability and provide benefits for consumers.